2018
DOI: 10.1186/s12939-018-0837-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential achievements in childhood immunization across geographical regions of Pakistan: analysis of wealth-related inequality

Abstract: BackgroundChildhood immunization is one of the most cost-effective interventions for child health. Still, many children are not able to receive completed immunization status. Wealth – related inequality in immunization is considered a major reason for equitable coverage of immunization in Pakistan. Therefore, we examine wealth-related inequality in completed childhood immunization and to assess achievement indices across geographical regions in Pakistan.MethodsThe analysis was based on a nationally representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
3
9
1
Order By: Relevance
“…Hence, women who always listen to the radio, watch tv and who were in position of a mobile phone, had higher odds of receiving the adequate doses of TT immunization compared to those with no access to the mass media. This is similar to previous studies in which mass media played an important role in increasing the odds of receiving adequate doses of TT immunization [34,36,37]. Recently, studies conducted in Vietnam and in sub-Saharan Africa also supported our findings and reported that women having access to media were more likely to receive adequate dose of TT immunization than those with no access [38,39].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, women who always listen to the radio, watch tv and who were in position of a mobile phone, had higher odds of receiving the adequate doses of TT immunization compared to those with no access to the mass media. This is similar to previous studies in which mass media played an important role in increasing the odds of receiving adequate doses of TT immunization [34,36,37]. Recently, studies conducted in Vietnam and in sub-Saharan Africa also supported our findings and reported that women having access to media were more likely to receive adequate dose of TT immunization than those with no access [38,39].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding adequate doses of TT immunization, women who made at least four ANC visits during the last pregnancy had higher odds of receiving two doses of TT immunization compared to those who attended fewer visits. This finding is consistent with those of studies conducted in Ethiopia, Bangladesh, India and Laos [29,37,43,44]. The plausible reason for this finding may be that women who have attended more ANC visits are more likely to be informed about the importance of TT immunization and would therefore receive it than those who attended less ANC visits.…”
Section: Discussionsupporting
confidence: 90%
“…Statistics from different sources in Pakistan have reported varying percentages of vaccination coverage, ranging from 40 to 80% with wide variations between provinces as well as between male and female children 22 . The higher percentages for vaccination coverage are generally reported by the government while some researchers and non-governmental agencies have reported low vaccination coverages across Pakistan over the time [23][24][25] . This variation may be attributed to the methodology adopted in collection of data (recall/record base data, estimation of the numerators/denominators), over/miss-reporting of the collected data, training/skill of the field teams and some other socio-geographical factors (parents' knowledge, religious beliefs and accessibility to health facility).…”
mentioning
confidence: 95%
“…The available data on vaccination coverage in Pakistan is limited and on many occasions faulty and over-estimated 30 . The available studies on vaccination coverage either discuss secondary data from surveys across Pakistan or are about one or few districts and predominantly about single antigen 25,[31][32][33] . Our study has tried to contribute in these lacking areas of spatial analysis on vaccination coverage across Pakistan.…”
mentioning
confidence: 99%
“…In addition, Pakistan is among the other LIMCs struggling towards meaningful increment in vaccination coverage; however, there exist socioeconomic inequalities in childhood vaccination coverage (Raza et al, 2018).…”
mentioning
confidence: 99%